Two replacement names of the genus group of Micronoctuini and a new species of the genus Tentaxus Han & Kononenko from Sabah, East Malaysia (Lepidoptera, Erebidae, Hypenodinae). Taxonomic study of Micronoctuini. Contribution I. - Han, H.l.; Kononenko, V.s. (Zootaxa, 2017)
Two replacement names of the genus group in Micronoctuini (Lepidoptera, Erebidae, Hypenodinae), Tentaxus nom. nov. pro Tentax Fibiger 2011 (unavailable name) and Flaxus nom. nov. pro Flax Fibiger 2011 (unavailable name) are proposed; 43 new conbinations (comb. nov.) are stated. A new species T. zhangweiweii Han & Kononenko, sp. nov. is described from Borneo (Sabah, East Malaysia).